Effects of gastrointestinal digested polyphenolic enriched extracts of Chilean currants (Ribes magellanicum and Ribes punctatum) on in vitro fecal microbiota. (March 2020) - Burgos-Edwards, Alberto; Fernández-Romero, Arantxa; Carmona, Manuel; Thuissard-Vasallo, Israel; Schmeda-Hirschmann, Guillermo; Larrosa, Mar
Graphical abstract: Highlights: Chilean Ribes polyphenols were digested and tested in an in vitro model of gut microbiota. Digested Chilean currants reduced branched chain fatty acids and SCFA throughout fermentation. Both digested Ribes promoted the growth of Clostridium cluster XIVa. Ribes punctatum increased Faecalibacterium prausnitzii population. Abstract: Chilean currants ( Ribes magellanicum and Ribes punctatum ) are wild polyphenol-rich berries with interesting bioactivities in several in vitro models. The aim of this study was to investigate the effects of the pre-digested PEE (polyphenol-enriched extract) in a simulated colon model. Fruits were extracted, submitted to simulated gastrointestinal digestion and further colonic fermentation with feces from healthy human donors. Samples were taken at 1, 4, 8 and 24 h of incubation, monitoring pH, ammonia, branched-chain fatty acids (BCFA), short-chain fatty acids (SCFA) and bacterial growth. FOS (fructooligosaccharides) and fecal slurry without treatments were positive and negative control, respectively. Both Ribes species reduced (p < 0.05) both BCFA and SCFA at 24 h. R. punctatum promoted the growth (p < 0.05) of beneficial bacteria such as Clostridium cluster XIVa, and Faecalibacterium prausnitzii ; while a trend to increase Akkermansia muciniphila was observed. R. magellanicum increased (p < 0.05) Clostridium cluster XIVa population. Escherichia coli, Lactobacillus spp. and Bifidobacterium spp. remained unaffected. Our results suggest that polyphenols from R. punctatum and R. magellanicum may modulate both bacterial metabolism and some selected gut beneficial bacteria under simulated conditions. Therefore, Chilean currants might be useful as supplements to maintain a healthy colon; however, further in vivo studies are needed to confirm their effect and their mechanisms.